Epidemiology and Inpatient Outcomes of Invasive Aspergillosis in Patients with Liver Failure and Cirrhosis - Aditya Sharma; Bashar Mohamad; Ayman O. Soubani (Journal of Fungi)
Objective: The aim of this study was to estimate the incidence and inpatient outcomes of liver failure and cirrhosis (LFC) admissions with invasive aspergillosis (IA) in the United States. Methods: This retrospective cohort study utilized the 2016–2020 National Inpatient Sample (NIS) database to analyze outcomes of IA in LFC admissions. Baseline variables, including demographics, comorbidities, and complications, were identified using International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) codes, and liver transplant admissions were excluded. Outcomes were compared between LFC admissions with and without IA. Results: During the study period, 9515 (0.36%) LFC admissions were associated with IA. This cohort experienced significantly higher rates of complications, including acute kidney injury (AKI) (73.36% vs. 42.96%; p < 0.001) and acute respiratory failure (ARF) (65.74% vs. 24.85%; p < 0.001). IA admissions required invasive mechanical ventilation (IMV) more frequently (58.17% vs. 18.78%; p < 0.001). All-cause inpatient mortality was significantly higher in the aspergillosis group (43.40% vs. 15.75%; p < 0.001). IA admissions had longer lengths of stay (LOS), with 38.89% exceeding 21 days compared to 6.20% (p < 0.001), and a mean LOS more than three times longer (22.9 vs. 7.5 days; p < 0.001). The IA group incurred over four times higher hospital charges (USD 459,414.9 vs. USD 104,389.4; p < 0.001) and hospitalization costs (USD 108,030.6 vs. USD 24,272.1; p < 0.001) compared to the LFC without aspergillosis group. Interpretation: LFC admissions with IA experienced poorer outcomes, longer hospital stays, and significantly higher healthcare costs, underscoring the need for targeted interventions in this high-risk, nonclassical population.